The Impact of Social Media on Public Outreach in the Fields of Education, Economy, and Health Based on Religious Values - Abdul Syukur; Dian Ferdiansyah; Nurul Latifah (Smart Society, 2024)
This study aims to examines the critical role of social media in public outreach within the fields of education, economy, and health, emphasizing its integration with religious values. Using a systematic literature review approach, this study analyzes academic sources, reports, and case studies to explore how platforms such as Facebook, Instagram, and YouTube facilitate the dissemination of faith-based content, particularly in Islamic contexts. The findings indicate that social media enhances religious education, supports Islamic economic practices (e.g., zakat distribution and halal investments), and promotes health awareness campaigns aligned with Islamic values of hygiene and wellness. However, challenges such as the digital divide in underprivileged communities, misinformation about health practices, and privacy concerns in faith-based financial transactions hinder the full potential of social media outreach. To address these issues, greater collaboration between religious institutions, government agencies, and social media platforms is necessary, particularly through digital literacy programs, content regulations, and joint awareness campaigns. Strengthening these efforts can ensure that social media serves as a powerful tool for community education, empowerment, and the promotion of religious values in modern society.